Anomalies of dielectric properties in a lithium-titanium ferrite ceramic; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Malyshev A. V. Andrei Vladimirovich (2012, 2012)
Title screen